2007
DOI: 10.1152/ajplung.00317.2006
|View full text |Cite
|
Sign up to set email alerts
|

Collagen I and thrombin activate MMP-2 by MMP-14-dependent and -independent pathways: implications for airway smooth muscle migration

Abstract: Henderson N, Markwick LJ, Elshaw SR, Freyer AM, Knox AJ, Johnson SR. Collagen I and thrombin activate MMP-2 by MMP-14-dependent and -independent pathways: implications for airway smooth muscle migration. Am J Physiol Lung Cell Mol Physiol 292: L1030-L1038, 2007. First published December 22, 2006; doi:10.1152/ajplung.00317.2006.-Increased proinflammatory mediators and ECM deposition are key features of the airways in asthma. Matrix metalloproteinases (MMPs) are produced by airway smooth muscle (ASM) cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 54 publications
3
53
0
1
Order By: Relevance
“…Legumain activates pro-MMP-2 by cleavage at the Asn 109 -Tyr and Asn 111 -Phe peptide bonds (17). Serine protease activation of pro-MMP-2, such as that mediated by thrombin and plasmin, has been well studied, with some reports indicating the involvement of MT1-MMP, which remains controversial (14,15,27,35,43,44). However, the detailed molecular mechanism for pro-MMP-2 activation by serine proteases remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Legumain activates pro-MMP-2 by cleavage at the Asn 109 -Tyr and Asn 111 -Phe peptide bonds (17). Serine protease activation of pro-MMP-2, such as that mediated by thrombin and plasmin, has been well studied, with some reports indicating the involvement of MT1-MMP, which remains controversial (14,15,27,35,43,44). However, the detailed molecular mechanism for pro-MMP-2 activation by serine proteases remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…We first speculated that MT1-MMP may be involved in this process because thrombin has been reported to activate pro-MMP-2 in an MT1-MMP-dependent manner (15,27). Thus, we examined MT1-MMP dependence in thrombin-mediated processing of pro-MMP-2 using a metalloprotease inhibitor and MT1-MMP-deficient cells, all of which provided evidence for non-MT1-MMP components at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some controversial reports suggest the involvement of membrane-type 1 MMP (MT1-MMP) in thrombin-mediated activation of pro-MMP-2 (19,(22)(23)(24). In our previous studies, we demonstrated that thrombin directly cleaved the propeptide on the C-terminal side of Arg 98 and Arg 101 with a preference for Arg 101 ; this was followed by intermolecular autoproteolytic cleavage at the Asn 109 -Tyr peptide bond, resulting in full enzymatic activation (7).…”
mentioning
confidence: 99%